Destabilization signs in behavioral and somatovegetative parameters of rats selected for catatonia - T. A. Alekhina; N. A. Palchikova; R. V. Kozhemyakina; O. I. Prokudina (Вавиловский журнал генетики и селекции, 2016)
The article presents data on destabilization signs in response to selection for catatonia at an organismal level. Experiments were conducted with the unique GC (genetic catatonia) rat strain selected for long passive-defensive freezing. The goal of this study was to detect destabilization signs in the behavioral and somatovegetative parameters of GC rats emerging in response to selection. The destabilization manifested itself as changes in rat attitudes towards humans, as became apparent from the glove test. Altered hormone levels in GC rats were detected: corticosterone concentrations were reduced in feces and increased during handling. The metabolic system showed a decrease in energy stored accompanying the fast (glucose level) and slow (triglyceride level) responses. However, the strains did not differ in the concentration of insulin, which affects glucose transport through the cell membrane. Nor did we find differences between Wistar and GC rats in cholesterol level. This lipid is important for both energy and constructive metabolism. A side effect of selection for catatonia was the worse pelage status in GC rats. The overall physical condition of catatonic rats involved reduced body weight in both neonates and adults. All these changes point to the modification of behavioral and somatovegetative patterns and intensification of the passive-defensive component of selection in GC rats.